The wicked big toddlah goes to New York - Hawkes, Kevin (New York : Alfred A. Knopf, 2011)
A Maine couple and their gigantic toddler take a trip to New York City, where despite his size, the "wicked big toddlah" becomes lost.
Maine author.
Keywords: Toddlers -- Juvenile fiction; Size -- Juvenile fiction; Missing children -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction